2010
DOI: 10.1016/j.annepidem.2009.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Disadvantage and Physical Activity: Baseline Results from the HABITAT Multilevel Longitudinal Study

Abstract: Neighborhoods may exert a contextual effect on the likelihood of residents participating in PA. The greater propensity of residents in advantaged neighborhoods to do high levels of total PA may contribute to lower rates of cardiovascular disease and obesity in these areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
96
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 50 publications
7
96
0
Order By: Relevance
“…Given that physical activity is an important predictor of obesity, this is worthy of discussion in the context of social determinants. The built environment plays a key role in terms of influencing physical activity in neighborhoods, with recent data showing a greater propensity for individuals residing in less disadvantaged areas to participate in more physically active lifestyles (12). However, given that our current study did not examine the role of physical activity on arthritis, we are only able at this point to speculate about the complexity between disadvantage measured at the neighborhood and individual levels and arthritis.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Given that physical activity is an important predictor of obesity, this is worthy of discussion in the context of social determinants. The built environment plays a key role in terms of influencing physical activity in neighborhoods, with recent data showing a greater propensity for individuals residing in less disadvantaged areas to participate in more physically active lifestyles (12). However, given that our current study did not examine the role of physical activity on arthritis, we are only able at this point to speculate about the complexity between disadvantage measured at the neighborhood and individual levels and arthritis.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, and as previously reported, the areal units employed for analysis within the HABITAT cohort were selected based on sampling convenience (36), and not reasons specifically related to arthritis prevalence; given this, we hypothesize that the potential impact of living in a disadvantaged neighborhood on the prevalence of self-reported arthritis would be underestimated. Nonresponse for the baseline HABITAT study was 31.5%, with greater nonresponse from individuals in more disadvantaged neighborhoods (12). The population was identified from the Commonwealth Electoral Roll, which has been reported as underrepresenting individuals who are disadvantaged, transient or homeless, and migrant (15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Such disparities are particularly apparent for recreational physical activity. A study in the Netherlands found that residents of low SES neighborhoods had a higher likelihood of not participating in recreational physical activity, in comparison to those of high SES areas.…”
Section: Introductionmentioning
confidence: 99%